WHICH HERNIA WHICH REPAIR? EXPERIENCE WITH PRE-PERITONEAL STOPPAS REPAIR: Pre-peritoneal Stoppa’s Repair - Tarar, Nasim Afzal; Munir, Shahid (Pakistan Armed Forces Medical Journal, 2008)
Objective: The objective is to evaluate an alternate hernia repair technique for complex, combined primary and recurrent groin hernias. Design of Study: Quasi – experimental study. Place and duration: Surgical unit II, Ward – III CMH Rawalpindi from Jan 2002 to Jan 2005. Patients and Methods: This study included forty patients having inguinal hernias with 31 to 70 years of age. Twenty patients having primary bilateral, 10 cases with recurrent hernia and 10 with complex hernias. Mean hospital stay ranged from 1-5 days with average 3 days. General anaesthesia was administered in 35 cases and spinal anaesthesia only in 5 cases. Mean operation time was 70 minutes (Range 45-110 min). Results: Recurrence was noted only in one case. There was no need of conversion to another technique where as no case had mesh infection. Minor wound complications such as seroma or erythema were noted in few cases without any peri operative death. Conclusion: Stoppa’s repair is safe, effective addition to surgeons armamentarium to treat complex, groin hernias. It provides